Ab initio investigation of pressure-induced structural transitions and electronic evolution of Th3N4. Issue 2 (2nd April 2020) - Zhang, Yue; Guo, Yongliang; Liao, Zhiguang; Liu, Changdong; Huai, Ping; Zhu, Zhiyuan; Ke, Xuezhi
ABSTRACT: The crystal structures, lattice dynamics, mechanical, electronic properties, and electron–phonon coupling of T h 3 N 4 under environmental conditions and high pressures have been studied by merging first-principles calculations and particle-swarm optimization algorithm. Four structures are identified for T h 3 N 4, including the R 3 ¯ m, I 4 ¯ 3 d, R 3 ¯, and C 2/ m phases, in which the I 4 ¯ 3 d, R 3 ¯, and C 2/ m phases are newly predicted. Their mechanical properties, including the Poisson's ratio σ, the elastic anisotropy factor A U, and the Pugh's ratio B / G, have been calculated and discussed. The results show that the R 3 ¯ m, I 4 ¯ 3 d, and R 3 ¯ phases of T h 3 N 4 behave ductile nature, while the C 2/ m phase behaves brittle nature. Among them, the I 4 ¯ 3 d phase of T h 3 N 4 almost exhibits completely anisotropic nature. Besides, our electronic band structure calculations show that the pressure-induced semiconductor-metal transition occurs following the I 4 ¯ 3 d to R 3 ¯ phase transition. Further, the electron-phonon coupling of the R 3 ¯ phase has been analyzed. The results we obtained are of significance to further understand the physical essence of T h 3 N 4 and its practical engineering applications.